Female Enrollment Trends in Engineering Programs: A Case Study of Logistics Management Engineering (2015–2024) - Quiroz Araujo, Belgica Sagrario; Gutierrez Miranda, Delmis Emilia (LACCEI, 2025)
The low participation of women in engineering programs remains a significant issue in higher education, particularly in disciplines traditionally dominated by men, such as those related to science, technology, engineering, and mathematics (STEM). Despite institutional and societal efforts to close the gender gap, women continue to face multiple structural, cultural, and social barriers that limit their access, retention, and advancement in these fields. In this context, this study focuses on analyzing the evolution of female enrollment in engineering programs offered by the Centro Universitario Tecnológico (CEUTEC), Tegucigalpa campus, during the period 2015–2024. Additionally, it specifically examines the experiences of students enrolled in the Logistics Management Engineering program, aiming to identify the factors that influence their choice of career, the challenges they face, and the strategies that could promote greater female participation in this field. The analysis is based on quantitative enrollment data, as well as qualitative and quantitative information collected through surveys administered to active students in the first semester of 2025 in the Logistics Management Engineering program. Through this mixed-methods approach, the study seeks to provide evidence to guide more inclusive institutional and educational policies, fostering greater gender equity in the field of engineering.